KAJIAN METODE TITRASI FORMOL DALAM PENGUKURAN PROTEIN SUSU SEGAR MELALUI VALIDASI METODE ANALISIS (VMA) - Hermawan Setyo Widodo; Jodi Susanto; Yusuf Subagyo; Afduha Nurus Syamsi; Merryafinola Ifani (ANGON: Journal of Animal Science and Technology, 2022)
Background. This research was conducted to determine the feasibility of the formol titration method in measuring protein content in fresh milk. Material and method. The material used in this study was a sample of fresh cow's milk. Standard milk was prepared by adding hydrolyzed casein to obtain protein content of 10%, 8%, 6%, 4% and 2%. Each standard was triplicate tested to obtain LOD, LOQ, accuracy and precision calculations. The data obtained is then presented descriptively. Results. The results obtained show that the formol titration method achieves an LOD value of 2.12%, LOQ of 6.41%, an accuracy rate of 145.56% and a precision of 2;4;6;8;10% are 3.58;4.40;3.12;3.58;2.58%. The resulting linear curve has a regression equation Y=2.0228X – 2.785 with an R2 value of 0.957. Conclusion. It can be concluded that the measurement of milk protein using the formol titration method is quite good, but less accurate because it tends to be overquantify.